GREEN INFRASTRUCTURE OBJECTS ACCOUNTING OF URBOECOSYSTEMS: METHODOLOGICAL AND APPLIED ASPECTS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The need to improve and develop methodical approaches to the accounting of green infrastructure objects is due to the lack of a unified system for determining the green infrastructure objects status of municipal territorial communities; the high dynamism of changes in the quality of the urbanized environment natural components and the economic conditions of society's existence; insufficiently regulated spatial development of cities and intra-system zoning and zoning of cities; lack of an ecosystem approach to the procedure of green infrastructure objects assessment and accounting.The purpose of the article: to justify the need in determine the green infrastructure objects status of urboecosystems, generalize methodical approaches to the accounting of such objects and develop proposals for their improvement.Results. The article substantiates the necessity of determining the green infrastructure objects status in municipal territorial communities, improving and developing methodical approaches to their accounting. The institutional prerequisites for the green infrastructure objects accounting of urban ecosystems, the tools of quantitative and quantitative-qualitative accounting of green spaces (interactive maps and plans, GIS accounting, mapping methods) that have gained practical application are considered. International approaches to the accounting of green infrastructure objects of urban ecosystems are analyzed. Current approaches that can be used for the identification of green infrastructure objects, their inventory, and certification have been identified, which allows us to assert the feasibility of considering green infrastructure as natural assets of the urban economy with all the prerequisites and consequences, namely, reflection in the General Development Plans, development strategies, plans and projects, accounting on the accounts of municipalities, distribution of responsibility for creation, operation, restoration, etc., which will be directly reflected in the green infrastructure management system. Proposals have been developed to fill in the criteria for quantitative and qualitative accounting of green spaces, which must be included in inventory lists, registers and passports of green infrastructure objects. As well as value indicators: book value, restoration value, improvement value, value increase, depreciation of green infrastructure objects. The experience of accounting implementation for the value indicators of green infrastructure objects ecosystem services is substantiated, since ecosystem capital is no less important than financial capital, and over time it will become the basis of the national wealth of the world countries.Conclusions. The green infrastructure formation is one of the strategic directions of the green course principles implementation in urban planning, and the accounting system of green infrastructure objects is an institutional environment element of the green cities functioning, information support for making management decisions that will contribute to the natural resources protection of urban ecosystems, and the quality improvement of the city`s residents living environment.
Keywords: urboecosystems, green infrastructure, accounting, book value, ecosystem services, urban development plans.